2005
DOI: 10.7498/aps.54.2202
|View full text |Cite
|
Sign up to set email alerts
|

Frictional property of wetting contact line and Wenzel’s behavior of solid surface tension

Abstract: Based on the static-friction model for solid-liquid-vapor contact line suggested by Adam and Jessop,one can calculate surface-tension coefficient of solids from the data of wetting angles, but the results depend on the friction condition adopted. Using the data reported on stainless steel and polypropylene samples as examples, we have compared the surface-tension coefficients given by the Mises yield condition and Amonton's friction law. It is found that only the latter pos sesses always the Wenzel behavior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Kamusewitz et al adopted Mises condition to calculate the contact angle hysteresis but found that contact angle did not increase with the increase of surface roughness, which was in disagreement with the experimental results. [28] Cao and Jiang [29] tried to adopt the Amoton condition to explain the formation of the contact angle hysteresis. However, they did not give an analytic relationship between contact angle hysteresis and parameters of surface morphology.…”
Section: Introductionmentioning
confidence: 99%
“…Kamusewitz et al adopted Mises condition to calculate the contact angle hysteresis but found that contact angle did not increase with the increase of surface roughness, which was in disagreement with the experimental results. [28] Cao and Jiang [29] tried to adopt the Amoton condition to explain the formation of the contact angle hysteresis. However, they did not give an analytic relationship between contact angle hysteresis and parameters of surface morphology.…”
Section: Introductionmentioning
confidence: 99%